Fast determination by Fourier-transform infrared spectroscopy of sugar–acid composition of citrus juices for determination of industry maturity standards. Issue 1 (2nd January 2016) - Clark, CJ
ABSTRACT: Predictive models using attenuated total reflectance/Fourier-transform infrared (ATR-FTIR) spectra of citrus juices have been developed for determination of soluble solids (SSC), titratable acidity (TA) and the Californian–Australian citrus industry BRIMA index. Generic models, developed using partial least squares regression, included fresh juices ( n = 326) from grapefruit, lemon, mandarin (plus hybrids tangelo and tangor), oranges and interspecific hybrids. The models cover the ranges 4.0–17.6 °Brix, 0.08%–6.96% TA and −332–212 BRIMA units. Root mean square errors of prediction were 0.18 °Brix, 0.055% TA and 4 BRIMA, respectively. Spectral data acquisition time was 52 s per sample. Further analysis of navel oranges ( n = 1470) demonstrated that improved models that analyse juices from single species give better prediction errors (0.12 °Brix, 0.027% TA, 3.1 BRIMA units) than generic models. It is suggested that FTIR analysis is a suitable replacement for manual titration for TA in countries where regulations allow adoption of new technologies, while simultaneously measuring SSC and industry maturity standards.